Invasive pleural malignant mesothelioma with rib destruction and concurrent osteosarcoma in a dog. Issue 1 (December 2015) - Tommaso, Morena; Rocconi, Francesca; Marruchella, Giuseppe; D'Angelo, Anna; Masci, Stefano; Santori, Domenico; Civitella, Carla; Luciani, Alessia; Boari, Andrea
Abstract A 7-year-old Dachshund was clinically examined because of a 10-day history of lameness in the left hind limb. On the basis of radiological and cytological findings, an osteosarcoma of the left acetabular region was suspected. The dog underwent a hemipelvectomy and osteosarcoma was diagnosed by subsequent histopathological examination. An immovable subcutaneous mass was noted on the left chest wall during the physical examination and non-septic neutrophilic inflammation was diagnosed by cytology. Forty days later, the dog showed signs of respiratory distress with an in-diameter increase of the subcutaneous mass up to 4 cm. Thoracic radiography and ultrasonography revealed pleural effusion and a lytic process in the fourth left rib. Furthermore, ultrasound examination revealed a mixed echogenic mobile structure with a diameter of around 2 cm floating within the pleural fluid of the left hemithorax close to the pericardium. The dog underwent surgery for anen bloc resection of the subcutaneous mass together with the fourth rib and the parietal pleura. Moreover, the left altered lung lobe, corresponding to the mobile structure detected by ultrasound, was removed. Based on cytological, histopathological, and immunohistochemical examinations, an invasive epithelioid pleural malignant mesothelioma was diagnosed.